The New Covid-19 Wave and the Psychological Distress Among Senior High School Students in Ghana - Adangabe, Amos Amuribadek; Agbakplor, Godfred; Dorgbetor, Alfred; Dogbey, Alice Emmanuella; Braimah, Mary; Annang, Louisa; Sam-Wiah, Juliet; Dadzie, Gilbert (Future Science / FSH-PH Publications, 2022)
The study explored the psychological experiences of Senior High School students and their coping strategies in selected Senior High Schools in Ghana in the wake of the third wave of Covid-19. Data for the study were purposely collected from 20 respondents using a semi-structured interview guide and analysed thematically. The findings of the study revealed that the majority of students in Senior High Schools are confused and have a feeling of anxiety whilst on campus in the wake of the third wave of Covid-19. It was further established that Senior High School students cope by building relationships with their teachers and as well with their colleagues in school and adherence to state laid down protocols. The contribution of Guidance and Counselling units in the schools played a great role in helping students cope psychologically.